(untitled) - Eades, Keith M. (New York, 2006)
The Solution-Centric Organization provides a comprehensive framework for moving companies away from a product/price orientation to a successful, solution-centric approach that includes sales, marketing, communication, and a problem-solving mentality.
Keywords: Selling,Sales management,Consumer satisfaction,Bán hàng,Quản trị bán hàng,Hài lòng khách hàng